A case of solitary orbital neurofibroma - Ulivieri, Simone; Luglietto, Davide; Cellini, Ludovica; Vaiano, Anna; Miracco, Clelia; Giorgio, Antonio (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Neurofibromas are tumors consisting of a proliferation of periph¬eral nerves that can affect almost any organ, soft tissue, bone or anatomical site. We report a case of a 49-old woman with localized orbital neuro¬fibroma, not related to neurofibromatosis. We performed a total resection using Ulivieri’s extended lateral approach, with no tumor recurrence at 6-month follow-up.